Neonatal Hypoxic Ischemic Encephalopathy and Planned Home Birth. (17th January 2022) - Buchanan, Christina; Kuo, Sheree; Minton, Lea; Lee, Men‐Jean; Choi, So Yung; Soon, Reni
Abstract : Introduction: As planned home births increase, emerging evidence on the perinatal outcomes of newborns who were planned hospital births versus planned home births has been inconsistent, and a growing number of states have attempted to legislate community births. We sought to determine whether an association exists between neonatal hypoxic ischemic encephalopathy (HIE), a complication of ischemic birth injury, and planned location of birth. Methods: A case‐control study design was used to compare data from neonates with HIE obtained from electronic health records at Kapiolani Medical Center for Women and Children in Honolulu, Hawaii, with data from neonates without HIE obtained from Hawaii state birth certificate data. A penalized backward stepwise logistic regression was performed to control for confounders. Results: We included 164 neonates with HIE and 656 neonates in the control group. The odds of having been a planned home birth were 2.77 times higher in neonates with HIE compared with those without HIE (95% CI, 1.05‐6.87). After adjusting for insurance, mode of birth, meconium fluid, maternal hypertension, and chorioamnionitis, neonates with HIE were still more likely to have been a planned home birth compared with those without HIE (odds ratio, 11.56; 95% CI, 1.37‐118.77). Discussion: Neonates with HIE were more likely to have been a planned home birth compared with neonates without HIE.